Rancang-Bangun Perangkat Silabus dan RPP Sains Kimia Bercirikan Model GI dengan Media Lingkungan untuk Siswa Kelas VII Sekolah Menengah Pertama - Rayandra Asyhar; Affan Malik; Zurweni Zurweni (Universitas Jambi, 2013)
A set of syllabus and lesson plans of science chemistry charaterizing group investigation (GI) model andenvironment as learning resources for 7th-grade students of SMP has been developed. The development theproduct was intended to design an active and joyful instructional process for 7th-grade students of SMP inlearning science chemistry. The procedure of the development adopted Hannafin and Peck model that consists ofthree phases. This model was started with a need assessment and analysis (phase 1), then was designing process(phase 2), and finally development and implementation in a real teaching (phase 3). According to experts thedeveloped products are characterized by GI with environmental media. The result of research showed that theproducts could improve student’s activities in learning process.